Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Praticing indigenous feminism: Resistance to Imperialism - Stewart-Harawira, Makere (Making space for aboriginal feminism, 2007)
This chapter is situated within the complexities of the new forms of imperialism that characterize a world seemingly gone mad. The conviction that both the project of decolonization and that of human survival and ultimately, peace for a world hovering on the brink of self-destruction require, at the very least, the return of the feminine principle and in the process, right balance and the compassionate mind, to the center of our political ontologies, is central to this chapter. The thesis is two-fold: firstly, that Indigenous women have a vital role to play in the realization of alternative models of “being in the world‟ and secondly, that this represent a particularly poignant paradox.
Keywords: OFDIG; approches et analyses; discipline; femmes*; féminisme autochtone; impérialisme; militance; ressource en ligne; science politique; science politique et droit; sofia; thématiques